2010
DOI: 10.1038/emboj.2010.211
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity of Alzheimer's disease Aβ peptides is induced by small changes in the Aβ42 to Aβ40 ratio

Abstract: The amyloid peptides Ab 40 and Ab 42 of Alzheimer's disease are thought to contribute differentially to the disease process. Although Ab 42 seems more pathogenic than Ab 40 , the reason for this is not well understood. We show here that small alterations in the Ab 42 :Ab 40 ratio dramatically affect the biophysical and biological properties of the Ab mixtures reflected in their aggregation kinetics, the morphology of the resulting amyloid fibrils and synaptic function tested in vitro and in vivo. A minor incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
413
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 473 publications
(442 citation statements)
references
References 61 publications
28
413
0
1
Order By: Relevance
“…Traditionally, it was believed that Aβ1-42 is predominately responsible for toxicity observed in AD. Two key observations support this theory: 1) familial AD mutations in APP elevate the expression of Aβ1-42 [24,25]; and 2) Aβ1-42 is more prone to aggregation and is more toxic than Aβ1-40 [26,27]. However, it was reported that pyroglutamate-Aβ, which is also presented in AD plaques, could also be the toxic isoform of Aβ [28][29][30][31].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 92%
“…Traditionally, it was believed that Aβ1-42 is predominately responsible for toxicity observed in AD. Two key observations support this theory: 1) familial AD mutations in APP elevate the expression of Aβ1-42 [24,25]; and 2) Aβ1-42 is more prone to aggregation and is more toxic than Aβ1-40 [26,27]. However, it was reported that pyroglutamate-Aβ, which is also presented in AD plaques, could also be the toxic isoform of Aβ [28][29][30][31].…”
Section: Challenges In Targeting Amyloidmentioning
confidence: 92%
“…We cannot rule out the possibility that this result is secondary to the structure of the split Gluc constructs, but Shanker et al (10) report, using endogenous A␤, that heterodimers are rare. Recently A␤ oligomers made by a mixture of synthetic A␤40 and A␤42 (ratio 7:3) was found to be more stable and neurotoxic compared with A␤40 or A␤42 solo oligomer (32). A␤40 and A␤42 is also reported to coassemble into amyloid fibrils (33,34), suggesting that A␤40 or A␤42 homo oligomer may be mixed and may form further aggregated structures.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with recent reports suggesting that FAD-mutant presenilins can cause a reduction in the conversion of A␤43 and A␤42 to A␤40 and A␤38, respectively (7,25). This loss of carboxypeptidase function results in a gain of function; that is, the elevation of the critical A␤42/A␤40, thereby increasing the propensity of A␤ to aggregation and neurotoxicity (36). It should be noted that this specific loss of function also elevates longer A␤ peptides (7,14) and that the gain of neurotoxic function may be through these forms of A␤.…”
Section: Discussionmentioning
confidence: 99%